Challenges and frictions in the implementation of the CEFR-M: a conceptual paper - Saiful Islam, Ahmad Sukri; Zubairi, Ainol Madziah; Saad, Mohammad Azannee; Preece, Abdul Shakour Duncan (Akademi Pengajian Bahasa, UiTM, 2024)
Undeniably, there have been a lot of English language educational innovations in Malaysia since 1970, mainly aimed at improving learners’ English language skills. The most recent development is the incorporation of the Common European Framework of Reference for Languages (CEFR) into Malaysian English language curricula at all levels of education from pre-school to university. This move is in line with the country’s long-term commitment to raise the bar for students’ English proficiency, as articulated in the Malaysian Education Roadmap 2013-2025 and further accentuated in the 10-year Reform of English Language Education in Malaysia: The Roadmap 2015-2025. The implementation of the CEFR has entered the final phase of reform and has not been without challenges and frictions since its official introduction to primary and secondary education in 2017. Drawing upon 22 studies pertinent to the CEFR implementation in Malaysia, this paper aims to bring to the fore the challenges encountered in the implementation of the CEFR in the local context, which may reverberate with similar problems in other countries pursuing the same educational agenda. The paper ends with implications worth reflecting upon to better manage and improve the CEFR-M implementation.